2021
DOI: 10.1002/aenm.202101884
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Infrared Micro and Nanospectroscopy for Discharge Chemical Composition Investigation of Non‐Aqueous Lithium–Air Cells

Abstract: Metal–air batteries, such as Li–air, may be the key for large‐scale energy storage as they have the highest energy density among all electrochemical devices. However, these devices suffer from irreversible side reactions leading to battery failure, especially when ambient air is used as the O2 source, so a deep understanding over the surface chemistry evolution is imperative for building better devices. Herein, a multi‐scale (nano‐micro) FTIR analysis is made over the electrode surface during cell discharge em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The degradation of DMSO in potentials greater than 5.00 V is widely reported in the literature, 19,51,52 which is attributed to the organic solvent molecules reaction with water traces present in the samples. Mozhzhukhina et al 51 indicated the beginning of DMSO degradation at 4.30 V over a Pt electrode and the formation of dimethylsulfone.…”
Section: Electrochemical Analysismentioning
confidence: 73%
“…The degradation of DMSO in potentials greater than 5.00 V is widely reported in the literature, 19,51,52 which is attributed to the organic solvent molecules reaction with water traces present in the samples. Mozhzhukhina et al 51 indicated the beginning of DMSO degradation at 4.30 V over a Pt electrode and the formation of dimethylsulfone.…”
Section: Electrochemical Analysismentioning
confidence: 73%
“…Moreover, there were no Raman bands related to dimethyl sulfoxone (DMSO 2 ) in the spectrum which indicates that no DMSO oxidation was detected. DMSO 2 Raman bands should appear at 500 and 1130 cm –1 …”
Section: Resultsmentioning
confidence: 99%
“…DMSO 2 Raman bands should appear at 500 and 1130 cm −1 . 48 The morphologies of the pristine air electrode and after the deep discharge using DMSO were analyzed by SEM, at the oxygen channel side, 49 and are shown in Figure 5. Comparing the electrodes from the best performance for the open (Figure 5b; Figure S9b) and closed system (Figure 5c; Figure S10b) with the pristine electrode (Figure 5a; Figure S11), the presences of spherical particles and flake-like agglomerated were observed and can be attributed to mixed LiOH and Li 2 O 2 , as reported by Zeng et al, 9 and identified through Raman analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Li 2 O 2 is the main expected product for an aprotic Li–O 2 battery and the mechanism proposed by most studies involves an initial oxygen reduction (Eqn (1)), followed by Li + complexation (Eqn (2)) and lithium superoxide (LiO 2 ) disproportionation (Eqn (3)) to yield Li 2 O 2 . 6,20,38 Peng and co-workers highlighted LiO 2 intermediate formation using surface enhanced Raman spectroscopy (SERS) at a gold electrode in an acetonitrile-based electrolyte. 39 In our results, the characteristic superoxide band was not observed, probably because it remained in solution at low concentrations with a short lifetime.…”
Section: Resultsmentioning
confidence: 99%